Action-Potential Modulation During Axonal Conduction - Sasaki, Takuya; Matsuki, Norio; Ikegaya, Yuji (Science (American Association for the Advancement of Science), 2011)
Once initiated near the soma, an action potential (AP) is thought to propagate autoregeneratively and distribute uniformly over axonal arbors. We challenge this classic view by showing that APs are subject to waveform modulation while they travel down axons. Using fluorescent patch-clamp pipettes, we recorded APs from axon branches of hippocampal CA3 pyramidal neurons ex vivo. The waveforms of axonal APs increased in width in response to the local application of glutamate and an adenosine A₁ receptor antagonist to the axon shafts, but not to other unrelated axon branches. Uncaging of calcium in periaxonal astrocytes caused AP broadening through ionotropic glutamate receptor activation. The broadened APs triggered larger calcium elevations in presynaptic boutons and facilitated synaptic transmission to postsynaptic neurons. This local AP modification may enable axonal computation through the geometry of axon wiring.